Penyuluhan Kesehatan Tentang Cuci Tangan Pakai Sabun di SD Negeri Meteseh - Diana Dayaningsih; Dwi Mulianda; Anggraeni Widya Purwasih; Adelia Putri; Pravitasari Pravitasari; Iqbal Wisnu Pradana; Matius Ariel Jarwanto (Compromise Journal Community Proffesional Service Journal, 2024)
World Handwashing Day with Soap is a global campaign launched by the United Nations in collaboration with other organizations, both government and private, to promote the behavior of washing hands with soap by the public as an effort to reduce the mortality rate of children under five and prevent diseases that can have an impact on decreasing the quality of human life. Hand washing is the most important basic technique in the prevention and control of infections. Almost everyone understands the importance of washing hands with soap, but there are still many who do not get used to doing it right at the crucial moment. People will be able to increase their knowledge of healthy living wherever they are if they are aware, motivated and supported by information and health facilities and infrastructure. The results of the initial assessment at SD Negeri Meteseh Semarang found that 67% of students of SD Negeri Meteseh had experienced diarrhea, 66% of students did not know the meaning of diarrhea, 80% of students did not know about the causes of diarrhea, 81% of students did not know the signs and symptoms of diarrhea, 75% of students did not wash their hands before and after bowel movements and bowel movements, 78% of students did not wash their hands with soap. Washing hands with soap is very important as one way to prevent diarrhea, a WHO study of washing hands using soap can reduce the incidence of diarrhea by 47%. Based on the results of the study, interviews and observations while at SD Negeri Meteseh, the idea to conduct health counseling came up, namely washing hands with soap through providing direct information to all residents of SD Negeri Meteseh through the program "Wash Your Hands and Kill Your Germs". It is hoped that with this program, especially children at SD Negeri Meteseh will have a good habit, namely washing their hands with soap to kill germs that lodged in their hands and positive support from the school as a form of community service of STIKES Kesdam IV / Diponegoro Semarang.